Approach speed and performance in the horizontal jumps: what do Brazilian athletes do? - Alfano Mouro, N.; Fernandes de Paula Moura, T.; Paulo Borin, J. (New Studies in Athletics, 2005)
Take-off velocity is an important factor determining performance in the long jump and triple jump, and it is influenced by approach velocity. The objectives of this study were: a) to determine the relationship between approach velocity and jumping performance, b) to verify if approach velocity is different when we compare the long jump and triple jump, and c) to discuss individual relationships, in comparison with values achieved by the group of athletes studied. Thirty-two male athletes competing in Troféu Brasil de Atletismo 2003 were studied. The official results and the mean velocity measured at the last 5m of the approach run were investigated. High correlation values were found between approach velocity and long jump performance (r = 0.72), but this relationship was not as high for the triple jump (r = 0.58). Approach velocity shows a tendency to be higher in the long jump than at the triple jump, even though the difference is not statistically significant. Individual relationships show a tendency to be lower than the group relationship. In some cases, they are negative.